Qisas dalam Islam: Konsep, Mekanisme, dan Hikmah Pensyariatannya - Muhammad Fadhil (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Punishment is an important instrument in maintaining social order and preventing crime. In Islamic law, one form of punishment that plays a fundamental role is qisas, which is retribution for the crimes of murder and abuse. This concept is often misunderstood as a practice of violence, when in fact it embodies the principles of justice, protection of life, and social balance. Qisas is based on equality between the perpetrator and the victim, but its application is regulated by strict conditions and still allows for forgiveness and diyat compensation. This study aims to provide a comprehensive understanding of the essence of qisas, including its definition, normative basis, conditions for implementation, and the wisdom contained therein. The research method used is a literature review, tracing classical and contemporary tafsir and fiqh literature, as well as related academic research. The results of the study show that qisas has a universal dimension of justice that is not limited to certain communities, and affirms the importance of protecting the rights of victims while providing opportunities for social reconciliation through forgiveness. In addition, qisas serves as a deterrent to crime and a guarantor of social stability. This study affirms that qisas is not merely a punishment, but an ethical and juridical system that reflects the main objectives of Islamic law in protecting life and upholding justice.